Mahasiswa KKN sebagai Fasilitator Pembelajaran Qur’ani di Rumah Tahfiz Al Fatihah Talang Jambe - Naufal Rafid; Ikmal Muzadi; Desa Yekha (Fakultas Ushuluddin dan Komunikasi Islam, 2025)
Abstract The Community Service Program (KKN) Rekognisi is a form of student service to the community. This article aims to describe the role of KKN Rekognisi students from UIN Raden Fatah Palembang as facilitators in Qur’anic learning at Rumah Tahfidz Al Fatihah, Talang Jambe. The students did not only act as teachers but also as companions and motivators in creating an active, enjoyable, and meaningful learning environment. The approach used was participatory and educational, adjusted to the level of the students, most of whom are elementary school-aged children. The learning activities included the introduction of Arabic letters (huruf hijaiyah), reading from Iqra’ books, memorization of short surahs, and practicing Qur’anic manners. The results of the program showed an increase in the students’ motivation to learn and their ability to read the Qur’an, along with the development of a positive emotional bond between the students and the KKN participants. The role of students as facilitators in Qur’anic learning proved to have a positive impact on the development of Islamic education in non-formal institutions such as Rumah Tahfidz..